Corrosion Behavior and Biocompatibility of Na2EDTA-Induced Nacre Coatings on AZ91D Alloys Prepared via Hydrothermal Treatment - He, Meifeng; Lu, Wenbing; Yu, Dan; Wang, Hao; Wang, Shuai; Yuan, Chenggong; Chen, Aiying (Frontiers in Chemistry, 2022)
An effective method for controlling the corrosion rate of Mg-based implants must be urgently developed to meet the requirements of clinical applications. As a naturally occurring osteoid material, nacre offers a strategy to endow biomedical Mg alloys with excellent biocompatibility, and corrosion resistance. In this study, pearl powder and NaH2PO4 were used as precursors to deposit coatings on AZ91D alloy substrates hydrothermally based on Na2EDTA-assisted induction. Na2EDTA-induced nacre coatings were fabricated at various pH values, and its chemical composition and microstructure were analyzed via energy-dispersive X-ray, scanning electron microscopy, and X-ray diffraction spectroscopy. The corrosion-resistant performance and cytocompatibility of the samples were evaluated via electrochemical measurements and in vitro cell experiments. Results showed that the samples hydrothermally treated under faint acid conditions present excellent corrosion resistance, whereas the samples treated under slight alkaline conditions demonstrate improved biocompatibility due to high Ca and P content and large Ca/P atomic ratio. This study provides substantial evidence of the potential value of nacre coatings in expanding the biological applications of implanted biomaterials.